The influence of early life experiences on English and Australian Super League coaches' learning. Issue 2 (12th February 2021) - Holmes, Pete; Light, Richard L.; Sparkes, Andrew
ABSTRACT: This article focuses on the influence of early life experiences and socio-cultural context on coach learning in the sport of rugby league. It draws on the findings of a study that investigated the influence of cultural context on the development of elite-level rugby league coaches in England and Australia. The article focuses on the influence of experience from early childhood to the end of compulsory schooling on the development of three English and three Australian rugby league coaches who, at the time of the study, were working, or had worked, in the Super League.